Ethnic differences in GRHPR mutations in patients with primary hyperoxaluria type 2. (5th November 2013) - Takayama, T.; Takaoka, N.; Nagata, M.; Johnin, K.; Okada, Y.; Tanaka, S.; Kawamura, M.; Inokuchi, T.; Ohse, M.; Kuhara, T.; Tanioka, F.; Yamada, H.; et al.
<x xml:space="preserve">Abstract</x> The objective of this study was to investigate ethnic differences in the glyoxylate reductase/hydroxypyruvate reductase (GRHPR) gene in patients with primary hyperoxaluria type 2 (PH2). GRHPR was genotyped in Japanese patients with PH2 and all GRHPR mutations described to date were reviewed in terms of geographic and ethnic association. We identified a novel mutation, a two‐nucleotide deletion (c.248_249delTG) in exon 3 creating a premature 'stop' at codon 91. Also, we found that the c.864_865delTG mutation was associated with the rs35891798 single‐nucleotide polymorphism. The allelic frequencies of the c.103delG, c.494G>A, c.403_404+2 delAAGT, and c.864_865delTG mutations in PH2 patients were 37.8%, 15.6%, 10.0%, and 10.0%, respectively. All patients with the c.103delG mutation were Caucasian. Patients with the c.494G>A mutation and 78% (7/9) of those with the c.403_404+2 delAAGT mutation were from the Indian subcontinent, whereas those with the c.864_865delTG mutation were Chinese or Japanese. Molecular analysis of GRHPR of four Japanese PH2 patients identified a novel mutation (c.248_249delTG in exon 3). Caucasians with PH2 should be screened for the c.103delG mutation; patients from the Indian subcontinent for c.494G>A; and patients of East Asian origin (particularly) for c.864_865delTG. The prevalence of the latter mutation in PH2 patients from East Asia was 75.0%.